Speaking an additional language: Can study abroad do the trick? - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s María Juan-Garau Universitat de les Illes Balears, Spain   ABSTRACT The present article sets out to provide an overall picture of the acquisition of speaking abilities in a given second language acquisition (SLA) learning context, namely study abroad (SA), so as to ascertain whether SA can indeed 'do the trick', as it is popularly assumed, and, if so, under which conditions. Section 1 will characterise the SA context and look at how it can affect oral performance, bearing in mind the opportunities for target language contact and practice it offers learners. Section 2 will focus on the specific linguistic benefits in the oral domain that can accrue in this learning context. In this regard, we will present an overview of empirical research findings with special attention to the SALA (Study Abroad and Language Acquisition) and COLE (Context, Contact and Competence Level) research projects. Section 3 will concentrate on individual variables that may affect oral development abroad in combination with external variables such as SA programme conditions. Finally, Section 4 will provide a summary of the main ideas presented and draw some conclusions.